2021
DOI: 10.1080/15538362.2021.1975607
|View full text |Cite
|
Sign up to set email alerts
|

Application of Calcium Chloride at Different Phenological Stages Alleviates Chilling Injury and Delays Climacteric Ripening in Peach Fruit during Low-Temperature Storage

Abstract: Owing to the high degree of perishability of the fruit, the peach industry faces serious challenges tackling physiological disorders, microbial/chemical decay, and the suboptimal quality of the fruit during and following cold storage. The present study was aimed to investigate the effects of spray applications of calcium chloride (CaCl 2 ) at various physiological stages of fruit growth and development, on ripening, flesh softening, chilling injury (CI) and nutritional quality of peach fruit cv "Flordaking" du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…Preharvest application of calcium and salicylic acid on "Florida king" peaches increased fruit firmness as compared with control treatment (Ali et al, 2014). Similar results were obtained by Ali et al (2021 andAbd El-Aziz et al (2021).…”
Section: Discussionsupporting
confidence: 89%
“…Preharvest application of calcium and salicylic acid on "Florida king" peaches increased fruit firmness as compared with control treatment (Ali et al, 2014). Similar results were obtained by Ali et al (2021 andAbd El-Aziz et al (2021).…”
Section: Discussionsupporting
confidence: 89%
“…In 2020, organic Ca or CaCl 2 increased the FF in the fruit of Kato Lehonia or Agios Vlasios, respectively. Similarly, in previous studies, CaCl 2 application increased FF [22,31]. In another study, the control and Ca-sprayed peaches had similar FF at harvest, but after cold storage, the Ca-sprayed fruit had higher FF values compared to the untreated peaches [21].…”
Section: Fruit Quality Characteristicssupporting
confidence: 74%
“…In general, the effect of foliar Ca applications on the fruit quality was not clear. Ali et al [22] and Val and Fernández [24] mentioned that CaCl 2 did not influence SSC, while Wahab et al [31] observed an increase in SSC with fruit from different peach cultivars. Moreover, the TA level in peach fruit was not affected [21], increased [22], or decreased after CaCl 2 foliar applications [31].…”
Section: Fruit Quality Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, [26,27] stated that high doses of calcium reduced ethylene creation in apple slices by impeding the transfer of 1-aminocyclopropane-l-carboxylic acid (ACC) to ethylene. The use of CaCl 2 markedly declined the prevalence of chilling injury and prolonged the climacteric maturation by reducing the ethylene making levels and fruit softening during storing compared to control [28].…”
Section: Introductionmentioning
confidence: 98%